Makna Syair Lagu Sakura Dalam Dua Lagu J-Pop Berjudul Sakura Karya Naotaro Moriyama dan Kentaro Kobuchi - Aulia Praharsacitta, Clarissa (Humanis, 2017)
Sakura is a flower that truly loved by the Japanese. The Sakura flower is beloved by Japanese as the pride symbol. This research is about the meaning of the Sakura song lyrics in two songs titled Sakura by Naotaro Moriyama and Kentaro Kobuchi. The method used in this research is descriptive analysis method and informal method. The theory used in this research is semiotics Riffatere by Riffatere. Based on the analysis, the meanings of the Sakura song lyrics by Naotaro Moriyama are friendship and parting with a friend. The Meaning of the Sakura song l yrics by Kentaro Kobuchi are love, farewell and sadness because can not be with the loved ones.
Keywords: Sakura, semiotika Riffatere, farewell